The role of the principal concerning the professional development of teachers in closing the achievement gap among students - Mohamed, Nasir (2012)
The achievement gap among students has become a big concern in many schools in recent years. The slow learners, who are the majority of students, show very low level of achievement. The aim of this study is to better understand the role played by the principal in organizing professional development programmes for teachers and ensuring the learning of all children to reduce the achievement gap. The findings of this study show that training teachers to cater the individual need of students will help to close the achievement among students. It also indicates that the principal has a direct and practical role in the design, delivery and content of the professional development of teachers.